Purification of High Free Fatty Acid Crude Palm Oil Using Molecular Distillation - Japir, Abd Al-Wali; Salimon, Jumat; Derawi, Darfizzi; Bahadi, Murad; Yusop, Muhammad Rahimi (Asian Journal of Chemistry, 2016)
The separation of free fatty acid (FFA) from high free fatty acid crude palm oil (HFFACPO) was done by using molecular distillation (MD). The separation parameters was at their boiling points; a feed amount of 2.3 mL/min; an operating pressure of 10 Torr; a condenser temperature of 60 °C; and a rotor speed of 300 rpm. The physico-chemical characteristics of HFFACPO and purified crude palm oil (PCPO) were determined. The results showed that the percentage of free fatty acid decreased from 8.7 ± 0.3 to 0.9 ± 0.1 %; iodine value from 53.1 ± 0.4 to 52.7 ± 0.5 g I2/100 g; hydroxyl value from 32.5 ± 0.6 to 13.9 ± 1.1 mg KOH/g; unsaponifiable value from 0.31 ± 0.01 and 0.20 ± 0.15 %; moisture content from 0.31 ± 0.01 to 0.24 ± 0.01 % for HFFACPO and PCPO, respectively. Gas chromatography (GC) results showed that the major fatty acids in crude palm oil (CPO) were palmitic acid (44.4 %-45 %) followed by oleic acid (39.6 %-39.8 %). High performance liquid chromatography (HPLC) results showed that the major triacylglycerol (TAG) were POP (30.8-32.4 %) followed by POO (24.9-25.1 %). In general, PCPO showed admirably physico-chemical properties and the quality of purified oil was completely improved.